A cross-cultural analysis of attributes that influence customers’ hotel experience in green hotels - Bernard, S.; Ho, J. A.; Dias, Á.; Zizka, L.; Singal, M. (Journal of Travel Research, 2026)
Although there is increasing awareness of hotels’ sustainability efforts, there are gaps in understanding both how and when green practices influence guest evaluations. To address this gap, this study applies the complexity theoretical framework and fsQCA to examine key attributes that influence guest experiences as reflected in online reviews of green hotels. In our study, emotions emerged as a critical attribute, surpassing the impact of sustainability measures. Results indicate specific combinations of hotel characteristics, such as ratings and sustainability practices as well as socio-cultural factors like collectivism and gender, drive positive and negative feedback in hotels. An intervention model for hotel managers to encourage pro-environmental behavior of guests is proposed based on their attribute grouping. Different strategies such as social norm messaging, co-creation with customers, and status signaling, will encourage guests to recognize and highlight sustainability practices in online reviews.